Electrostatic Field of „Wire-to-Cylinder“ Electrode System - Žebrauskas, S.; Marčiulionis, P. (Elektronika ir Elektrotechnika, 2005)
If the DC corona field is being analysed by the Deutsch‘s- Popkov‘s method the functions of distribution of electrostatic field strength on the axis of symmetry and on the surface of wire is needed. The comparable analysis of electrostatic field in the electrode system „wire-to cylinder“ and „wire-to-plane“ is given. The maximum difference of potentials on the axis of symmetry of these two elektrode systems is 15 %, the maximum difference for field strength on the axis of symmetry is 17 %. Therefore electrostatic field in the system „wire-to- cylinder“ isn‘t equivalent to the the field in the system „wire-to-plane“. The maximum difference of electrostatis field strength on the surface of the wire for both systems is 3,7 %, whereas the variation of the field strength in each of the systems of electrodes does not exceed 1,2 %. Ill.3, bibl. 9 (in Lithuanian; summaries in Lithuanian, English and Russian).